Meleagris Gallopavo Algorithm for Solving Optimal Reactive Power Problem - K. Lenin (International Journal of Applied Power Engineering (IJAPE), 2018)
In this paper, Meleagris Gallopavo Algorithm (MGA) is proposed for solving optimal reactive power problem.As a group-mate Meleagris gallopavo follow their poultry to  explore food,  at the same time it prevent the  same ones  to eat their own food. Always the overriding individuals have the lead to grab more food and Meleagris gallopavo would arbitrarily pinch the high-quality food which has been already found by other Meleagris gallopavo. In the region of the mother Meleagris gallopavo, Poults always search for food. In the Projected Meleagris Gallopavo Algorithm (MGA) additional parameters are eliminated, in order to upsurge the search towards global optimization solution.Proposed Meleagris Gallopavo Algorithm (MGA) has been tested on two modes a. with the voltage stability Evaluation in standard IEEE 30 bus test system, b. Without voltage stability Evaluation in standard IEEE 30, 57,118 bus test systems & practical 191 test system. Simulation results show clearly the better performance of the proposed Meleagris Gallopavo Algorithm (MGA) in reducing the real power loss, enhancement of static voltage stability Index and particularly voltage profiles within the specified limits.